Efektifitas Otago Exercise Dan Ankle Exercise Terhadap Penurunan Resiko Jatuh Pada Lansia - Ulfatun Hasanah; H.Nur Hamim; Shinta Wahyusari (Pusat riset dan Inovasi Nasional, 2023)
The risk of falling can be a serious complication in the elderly because falls in the elderly can cause serious injury and disability. Handling that can be applied to reduce the risk of falling is by otago and ankle exercises. The purpose of this study was to analyze the effectiveness of otago and ankle exercises on reducing the risk of falling in the elderly in Tegalsiwalan Village, Tegalsiwalan, Probolinggo.This type of research is a pre experimental design with a pre post design approach. The population of 40 people with 36 respondents who met the inclusion requirements of the study, were selected by purposive sampling technique. The berg balance scale obsevatio sheet is the tool employed, and the data is subsequently gathered using the editing, coding, scoring and tabulating processes. The data obtained were analyzed using the Chi square and the Wilcoxon hypothesis test in both groups. The results showed that the p value was 0.002 in the group given the otago exercise and the p value was 0.014 in the group given the ankle exercise. For the comparison test, the value of sig(2-tailed) was 0.245 > 0.05. So there is no difference between otago exercise and ankle exercise in reducing the risk of falling in the elderly.The next researcher gave the same intervention both for group one and group two. So that further researchers can combine these two interventions, so that the result are maximized.